The Influence of Product Attributes on Organic Vegetable Purchase Decisions of Young Consumers Through Delivery Services - Pramudita, Ranatasya; Muhaimin, Abdul Wahib; Haryati, Novi; Maulidah, Silvana (Agro Bali : Agricultural Journal, 2025)
The growing awareness of health and environmental concerns has led to an increase in the consumption of organic vegetables, especially among young consumers. This study aims to identify key factors influencing their purchasing behavior and provide insights for improving business service strategies. Data were collected from 162 purposively selected students at Brawijaya University and analyzed using Structural Equation Modeling (SEM) with WarpPLS. The results indicate that product actuality has the strongest influence on purchasing behavior (effect size = 0.229, p < 0.05), followed by delivery service (0.153, p < 0.05). Delivery service is significantly affected by product actuality, quality, health issues, appearance, freshness, and taste, as well as curiosity and prestige (all p < 0.05). Mediating effects are also significant for product actuality and appearance (p < 0.1). These findings highlight the importance of ensuring authentic products and optimizing delivery services to enhance business performance in the organic market segment.